PHYSICAL MODEL OF HYBRID ENGINE WITH ROTARY INTERNAL COMBUSTION ENGINE - D’yachkov, V. V.; Shakirov, A. L. (Recent Contributions to Physics, 2009)
A physical model of hybrid engine (HE) applicable in vehicles power units designing has been developed. The model represents a rotary internal combustion engine (ICE) of a reciprocating rotary type connected to the dynamotor with a crank mechanism. Geometric proportions of the elements of the crank mechanism ensuring its reliable functioning and the required deviation amplitude of the crank have been determined.
Keywords: hybrid engine (HE)